Support for the integration of green roof constructions within Chinese building energy performance policies - Kokogiannakis, Georgios; Darkwa, Jo (Elsevier, 2014)
Green roofs could act as a thermal buffer in buildings and offer potential energy savings. However, the energy benefits from green roofs are not usually properly recognised by traditional building energy regulations. Building energy regulations are traditionally over-simplistic during the assessment of the energy performance of complex building constructions. In the case of green roof designs, it is essential that the assessment mechanisms should not ignore the complex heat and moisture balances within the green roof layers. In this paper, dynamic energy modelling that considers the complexity within the green roof layers is adopted to guide policy makers in China on the relationship between using specific thicknesses of roof insulation against green roof layers. Simulations are run for a residential building type by also considering different thermal envelope characteristics across eight large Chinese cities and within the five main climatic zones of China. Results that link the green roof characteristics with respective traditional insulation layers are produced for all cities and it is found that optimising the plant and soil characteristics of green roofs in some climates could substitute more than 125 mm of roof insulation, while less optimum green roof types could only replace about 25 mm of roof insulation.